The Feasibility Of East Asian Monetary Union As An Optimum Currency Area - Chee , Heong Quah (Penerbit Universiti Sains Malaysia (USM Press), 2009)
Monetary cooperation in East Asia has become increasingly important and practical, particularly in times of regional economic and financial crisis. Contrary to those papers of studies in the mainstream, this paper evaluates the feasibility of monetary union in East Asia by benchmarking its optimum currency area (OCA) criteria against selected dollarised countries and the European Economic and Monetary Union (EMU). Four criteria are proposed. The US dollar is designated as the anchor currency. To some extent, results do confirm the validity of the criteria and suggest a considerably strong case for monetary integration in parts of the region.